A new type of relief condenser for the study of microorganisms - Zizka, Z (Folia microbiologica, 2009)
A new type of relief condenser mounted on a current laboratory microscope produced by Lambda Praha was used for the study of microorganisms of two kingdoms, Chromista and Plantae. The pictures obtained by the use of this device had a better resolving power and remarkable contrast, and a well visible 3D effect. Because of the absence of an aperture diaphragm the use was much simpler, compared to relief condensers whose construction was different.
Keywords: rostlinné buňky; Microscopy; Eukaryota; mikroskopie; Plant Cells